2021
DOI: 10.19163/2307-9266-2021-9-1-17-31
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Hypericum Perforatum L. (Hypericaceae): A Review

Abstract: Федеральное государственное бюджетное учреждение науки Ботанический институт им. В.Л. Комарова Российской академии наук (БИН РАН) 197376, Россия, г. Санкт-Петербург, ул. проф. Попова, 2 2 Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский государственный химико-фармацевтический университет»

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…The least infiltration of inflammatory cells at 7 day interval was observed in HD. These findings were due to the fact that Hypericum contain Hypericin, which inhibited the pro-inflammatory enzyme janus kinase 1 (JAK1), and Hyperforin which inhibit the activity of cyclooxygenases (COX) 1 and 2 and prostaglandin synthase PGE2, which explained the anti-inflammatory properties of Hypericum [11]. Little inflammatory infiltration that noted in some samples at 14 day interval was probably due to selfmutilation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The least infiltration of inflammatory cells at 7 day interval was observed in HD. These findings were due to the fact that Hypericum contain Hypericin, which inhibited the pro-inflammatory enzyme janus kinase 1 (JAK1), and Hyperforin which inhibit the activity of cyclooxygenases (COX) 1 and 2 and prostaglandin synthase PGE2, which explained the anti-inflammatory properties of Hypericum [11]. Little inflammatory infiltration that noted in some samples at 14 day interval was probably due to selfmutilation.…”
Section: Discussionmentioning
confidence: 98%
“…Hyperforin, Flavonoids and Hypericin), which possess many pharmaceutical effects, the H. perforatum has been used both topically and orally to treat many conditions including skin wounds [7,8]. Literatures showed that it increased deposition of collagen and shortened the duration of inflammatory phase [9,10], also it has antibacterial activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hypericum perforatum L. is native Europe, western Asia, and northern Africa, although currently it has a worldwide distribution. H. perforatum is a species largely known for its antidepressant-like properties, nevertheless other proprieties have been reported such as neuroprotective, nootropic, antimicrobial, antiviral and antiprotozoal, antiepileptic, anxiolytic, antitumor and cytotoxic properties, analgesic, antiinflammatory and woundhealing properties, hypolipidaemic and hypoglycaemic properties, among other attributes (Oliveira et al, 2016;Budantsev et al, 2021). According to the Kraus et al (2007), the plant extract of H. perforatum was able to restore or improve microglial viability and thereby attenuate amyloid-β mediated toxicity in Alzheimer's disease, even better than individual flavonoids.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 99%